A review of component-in-the-loop: Cyber-physical experiments for rapid system development and integration - Haesul Fagcang; Richard Stobart; Thomas Steffen (2022)
To meet rising demands in performance and emissions compliance, companies are driven to develop systems of everincreasing complexity. In-the-loop methods use a hybrid approach combining a physical subsystem with a virtual subsystem in real-time that can make product development processes faster and cheaper, enabling physical subsystems to be tested in real-world conditions while they are immersed in virtual environment simulation. These techniques evolved from being used solely in controller development with only the embedded controller placed as hardware-in-the-loop (HIL), to being a more holistic technique for system synthesis, capable of both component- and system-level studies. This paper delves into the development of the latter form, henceforth referred to as “component-in-the-loop” or CIL. It provides a literature review of the growing uses of the technique in automotive development, giving a general implementation guidance in system architecture, methodology and control system structure. Furthermore, it suggests the need to clarify terminologies related to in-the-loop methods for a more efficient taxonomy. Definitions are proposed where deemed appropriate. In the age of search engines, this should facilitate knowledge transfer within and across disciplines. Finally, it highlights the key challenges in constructing such systems while discussing attempted solutions. CIL has reached a state of maturity where it is ready for wider adoption and continued technological progress will only push its potential further.